The Influence of the Constitutional Court Ruling No 90/PUU-XXI/2023 on the Authority and Marvel of the Constitutional Court as Guardian of the Constitution - Masdiah, Auliya Hanidatul; Kristanto, Budi (International Journal of Science and Society, 2024)
The Constitutional Court was formed to maintain the integrity of the Constitution through a deeper interpretation based on the 1945 Constitution. This journal discusses the influence of CC Decision No. 90/PUU-XXI/2023 on the Authority and Dignity of the Constitutional Court as Guardian of the Constitution. The study combines a literature review methodology with a qualitative approach. The research results show that CC Decision No. 90/PUU-XXI/2023 is contrary to the Constitutional Court's authority based on the 1945 Constitution. The addition of new regulations that were previously unregulated or not is not outside the Constitutional Court's jurisdiction, but rather the legislative authority. Research examines the importance of maintaining judicial neutrality to prevent abuse of power. The Constitutional Court, as the Guardian of the Constitution, must pay attention to the rights of citizens and maintain the balance of power. With this controversial decision, in the context of the CC authority which should be limited to constitutional review and maintaining the neutral role of the judiciary in fighting abuse of power by the legislature and executive. Even though the Constitutional Court is the final decision maker on laws based on the 1945 Constitution, its authority is limited to reviewing laws and is not involved in the legislative realm.